LÉLIA GONZALEZ - ENGLISH VERSION - Bastos, Morgana Abranches (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Lélia Gonzalez was a memorable black activist and intellectual. He studied and fought racism and sexism, studies that today are called intersectionality, but were already treated by Lélia before the word appeared. Lélia graduated in History and Geography, was a Master in Communication and a PhD in Political Anthropology. She was also one of the founders of the Unified Black Movement against Discrimination and Racism (MNUCDR) in 1978, which today is known as the Unified Black Movement (MNU). In addition, Lélia published numerous works that contributed and contribute to the discussions on the racial issue and black women in Brazil.